Patient with a rare weaker subgroup-A exhibiting ABO discrepancy: a case report - Yousuf, Rabeya; Yusof, Nurasyikin; Suhemi, Nur Afifah; Abdullah Thalith, Nor Fadzliana; Aziz, Suria Abdul (Bangladesh Journal of Medical Science, 2024)
Weaker subgroups have the potential to cause problems in the immunohaematological testing in the blood banks. We report here a case of rare weaker subgroup A, detected during the usual ABO grouping. A 49-year-old lady exhibited a discrepancy in the forward and reverse groupings. In forward-grouping, there was a mixedfield reaction with anti-A and anti-A,B while there was no reaction with anti-B. The reverse grouping showed no reaction with the A1 and A2 cells, but the reaction with B-cell was 4+. Further tests were performed and revealed a weaker subgroup of A. It is crucial to properly investigate and resolve any discrepancy in ABO grouping before commencing transfusion to avoid any wrong blood transfusion. This case report may assist others in resolving the ABO blood group discrepancies. Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 546-550